Pengaruh Media Sosial, Kepercayaan, Keterlibatan Konsumen, dan Loyalitas Terhadap Keputusan Pembelian Produk Fashion Skintific - Koyongian, Yeane; Walean, Ronny H.; Dungus, Jane (Syntax Corporation, 2025)
This study aims to explore the influence of social media, trust, consumer engagement, and loyalty on purchasing decisions of Skintific brand fashion products. With a quantitative approach, primary data was collected through an online survey using a Google Forms questionnaire. A total of 212 respondents, who are active users of social media and Skintific products, completed the questionnaire completely. Data analysis was carried out using SmartPLS 3 software with the SEM PLS method. Most of the respondents were aged 17-25 years old and the majority were women. The results showed that consumer trust had the most significant influence on purchasing decisions (coefficient of 0.476), followed by loyalty (0.350), while the impact of social media was smaller (0.098). Additionally, active consumer engagement contributes greatly to loyalty, as engaged consumers are more likely to be loyal to the brand. These findings underscore the importance of building trust and loyalty through meaningful interactions with consumers. This study recommends that Skintific prioritize transparency and improving product quality to strengthen consumer trust. Additionally, social media integration with comprehensive marketing strategies, loyalty programs, and interactive campaigns can increase consumer engagement and loyalty. This study provides valuable insights for practitioners and academics in understanding consumer behavior in the digital age.